Co-designing cryogenic system with pulse tube cryocooler and loop heat pipe for infrared energy management. (August 2021) - Guo, Yuandong; Zhou, Qiang; Liu, Xintong; Ding, Ting; Zhang, Hongxing; Fu, Zhendong; Miao, Jianyin; He, Jiang; Lin, Guiping; Li, Jindong
Highlights: The first co-designing cryogenic system in the world considering cryogenic acquisition and thermal transport is presented. Redundancy consideration of two cryocoolers and cryogenic loop heat pipes for engineering application was set in the system. Several thermal insulation measures were adopted to increasing the conversion efficiency for infrared energy management. Abstract: Cryogenic system is important for the infrared detectors, which can increase the ratio of signal-to-noise at low temperature. Long lifetime, high efficiency mechanical cryocoolers and two-phase heat pipes can reduce the energy consumption of the spacecraft and ensure a low weight. A co-designing cryogenic system consisting of two pulse tube cryocoolers (PTCs) and two neon cryogenic loop heat pipes (CLHPs) operating at temperature around 35 K is designed, manufactured, and tested in the present work. A novel integrated multifunctional heat exchanger is proposed to couple the heat exchange between the cold head of PTC and the condenser of CLHP. To our best knowledge, it is the first time to couple these two technologies directly for space application. The thermal design and efficiency analysis of this cryogenic system are presented, which optimize both the structural layout and insulation to reduce the heat load from surroundings. The thermal performance of the PTCs is ground tested and the co-designing cryogenic system is integrated in a vacuum chamber. The no-load temperatures of the PTCs are 25.3 K and 25.7 K, respectively, while both of the cooling capacities are over 2 W@35 K with the input power of 250 W AC. Meanwhile, the thermal performance of supercritical startup and steady-state operation are tested, and the results are discussed and analyzed.